American Planters and Irish Landlords in Comparative and Transnational Perspective : Lords of Land and Labor - Smith, Cathal (Routledge, 2021)
This is the first study to systematically explore similarities, differences, and connections between the histories of American planters and Irish landlords. The book focuses primarily on the comparative and transnational investigation of an antebellum Mississippi planter named John A. Quitman (1799-1858) and a nineteenth-century Irish landlord named Robert Dillon, Lord Clonbrock (1807-93), examining their economic behaviors, ideologies, labor relations, and political histories. Locating Quitman and Clonbrock firmly within their wider local, national, and international contexts, American Planters and Irish Landlords in Comparative and Transnational Perspective argues that the two men were representative of specific but comparable manifestations of agrarian modernity, paternalism, and conservatism that became common among the landed elites who dominated economy, society, and politics in the antebellum American South and in nineteenth-century Ireland. It also demonstrates that American planters and Irish landlords were connected by myriad direct and indirect transnational links between their societies, including transatlantic intellectual cultures, mutual participation in global capitalism, and the mass migration of people from Ireland to the United States that occurred during the nineteenth century.
Introduction: Comparing and Connecting Lords of Land and Labor 1. Ireland, the American South, and Rural Subjection, c. 1550-1800 2. The South's Second Slavery and Ireland's Second Landlordism: John A. Quitman's and Lord Clonbrock's Economic Attitudes and Behaviors 3. Planter and Landlord Ideologies: Quitman, Clonbrock, and Paternalism 4. Varieties of Paternalism in Practice: Labor Relations on the Quitman Plantations and the Clonbrock Estates 5. "We Have Become a Second Ireland": Landed Elites, Unionism, and Nationalism in the Antebellum South and Nineteenth-Century Ireland Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Quitman, John Anthony, -- 1798-1858.; Dillon, Robert, -- Baron, -- 1807-1893.; Plantations -- Southern States -- History -- 19th century; Plantation owners -- Southern States -- History -- 19th century; Land tenure -- Ireland -- History -- 19th century; Landlords -- Ireland -- History -- 19th century; Elite (Social sciences) -- Southern States -- History -- 19th century; Elite (Social sciences) -- Ireland -- History -- 19th century; Southern States -- History -- 1775-1865.; Ireland -- History -- 19th century; HISTORY / Europe / Ireland; HISTORY / United States / General; HISTORY / World